2022
DOI: 10.3389/fncel.2022.983577
|View full text |Cite
|
Sign up to set email alerts
|

Glial cells in anorexia

Abstract: Anorexia is a loss of appetite or an inability to eat and is often associated with eating disorders. However, animal anorexia is physiologically regulated as a part of the life cycle; for instance, during hibernation, migration or incubation. Anorexia nervosa (AN), on the other hand, is a common eating disorder among adolescent females that experience an intense fear of gaining weight due to body image distortion that results in voluntary avoidance of food intake and, thus, severe weight loss. It has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…The beginning of the light phase was at 6 AM. Female mice were used since a higher prevalence of AN in females is observed in humans [ 24 ]. All mice were housed individually in a cage and had unlimited access to a running wheel for the whole experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beginning of the light phase was at 6 AM. Female mice were used since a higher prevalence of AN in females is observed in humans [ 24 ]. All mice were housed individually in a cage and had unlimited access to a running wheel for the whole experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the POMC + cell densities in the ARC in ABA animals were increased [ 23 ]. Despite these reports, the reasons for changes in glial density due to starvation are unclear (reviewed in [ 24 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in animal models of AN, the density of astrocytic cells, as well as the expression of glial fibrillary acidic protein (GFAP), glutamate transporters (GLT-1 and GLAST), and glutamine synthetase, are reduced [ 18 , 76 ]. It was recently suggested that glial function is compromised by anorexia [ 77 ]. Therefore, it seems probable that dysfunctional glial cells produce lower quantities of KYNA.…”
Section: Tryptophan and Kynurenines In Anorexia Nervosamentioning
confidence: 99%
“…AN is associated with neuroendocrine and immune system abnormalities. For example, leptin, an essential appetite modulator involved in AN development, also regulates immune responses through microglia-induced inflammation by increasing the expression of tumor necrosis factor-α (TNF-α) and interleukin-1b (IL-1b) [18]. Additionally, activity-based anorexia (ABA), an AN model in rodents, reduces cortical astrocyte density, suggesting that astrocyte loss and subsequent neuroinflammation may be involved in the neurobiology of anorexia [19,20].…”
Section: Anorexia Nervosa (An)mentioning
confidence: 99%